Preliminary X-ray analysis of twinned crystals of the Q88Y25_Lacpl esterase from Lactobacillus plantarum WCFS1 - Álvarez, Yanaisis (International Union of Crystallography, 2011)
Q88Y25_Lacpl is an esterase produced by the lactic acid bacterium Lactobacillus plantarum WCFS1 that shows amino-acid sequence similarity to carboxylesterases from the hormone-sensitive lipase family, in particular the AFEST esterase from the archaeon Archaeoglobus fulgidus and the hyperthermophilic esterase EstEI isolated from a metagenomic library. N-terminally His(6)-tagged Q88Y25_Lacpl has been overexpressed in Escherichia coli BL21 (DE3) cells, purified and crystallized at 291 K using the hanging-drop vapour-diffusion method. Mass spectrometry was used to determine the purity and homogeneity of the enzyme. Crystals of His(6)-tagged Q88Y25_Lacpl were prepared in a solution containing 2.8 M sodium acetate trihydrate pH 7.0. X-ray diffraction data were collected to 2.24 Å resolution on beamline ID29 at the ESRF. The apparent crystal point group was 422; however, initial global analysis of the intensity statistics (data processed with high symmetry in space group I422) and subsequent tests on data processed with low symmetry (space group I4) showed that the crystals were almost perfectly merohedrally twinned. Most probably, the true space group is I4, with unit-cell parameters a = 169.05, b = 169.05, c = 183.62 Å.